International Spatial Diffusion of the Church of Jesus Christ of Latter-day Saints - Samuel M. Otterstrom (Territoire en Mouvement)
This paper outlines the international diffusion and growth of the Church of Jesus Christ of Latter-day Saints (Church members are commonly known as “Mormons”). A model of Mormon spatial diffusion in foreign countries is developed incorporating both a functional and spatial perspective. The functional perspective includes supply and demand variables which influence the rate of growth of Mormons within a country. The spatial perspective, which the study concentrates on, seeks to show a general spatial pattern related to the spread of the Church within countries. Included is a brief overview of the history of the international diffusion of the Church along with more in-depth spatial diffusion perspective analyses of Brazil, Peru, and Mexico. The research finds that the Church since World War II has diffused in a distinctly hierarchical manner within countries outside of the United States.